2014
DOI: 10.1061/(asce)wr.1943-5452.0000431
|View full text |Cite
|
Sign up to set email alerts
|

Reformulated Co-Tree Flows Method Competitive with the Global Gradient Algorithm for Solving Water Distribution System Equations

Abstract: Authors may post the final draft of their work on open, unrestricted Internet sites or deposit it in an institutional repository when the draft contains a link to the bibliographic record of the published version in the ASCE Civil Engineering Database. "Final draft" means the version submitted to ASCE after peer review and prior to copyediting or other ASCE production activities; it does not include the copyedited version, the page proof, or a PDF of the published version. Journal of Water Resources Planning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 12 publications
0
70
0
6
Order By: Relevance
“…An alternative to the GGA is the loop method [11], which is also a Newton-Raphson process working with a sparse, symmetric positive definite matrix. However, the size of the matrix is in this case n l ×n l , where n l = m−n is the number of independent loops that can be found in the network, which is usually much smaller that n. Some recent papers [5,7,10,2,1] have addressed the loop method as a competitive alternative to GGA. The authors developed contributions to this method, with the corresponding implementation [5].…”
Section: The Problem Of Wds Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative to the GGA is the loop method [11], which is also a Newton-Raphson process working with a sparse, symmetric positive definite matrix. However, the size of the matrix is in this case n l ×n l , where n l = m−n is the number of independent loops that can be found in the network, which is usually much smaller that n. Some recent papers [5,7,10,2,1] have addressed the loop method as a competitive alternative to GGA. The authors developed contributions to this method, with the corresponding implementation [5].…”
Section: The Problem Of Wds Simulationmentioning
confidence: 99%
“…Recently, several papers [7,8,10,2,1] have considered the loop method for simulation of WDS, first introduced in [11], as an alternative to the more widely used Global Gradient Algorithm (GGA), implemented in Epanet. The authors presented in [5] some contributions to the loop method, with an efficient implementation that is shown to be faster than Epanet for the test networks considered.…”
mentioning
confidence: 99%
“…However, in recent years new publications have shown that the loop method gives an efficient alternative to the hybrid approaches. Elhay et al (2014) use a tree-cotree decomposition and take advantage of the fact that loop methods are null space methods. Alvarruiz et al (2015) have shown that loops can be defined without tree-cotree decomposition to increase the sparsity of the iteration matrix.…”
Section: Alternative Formulationsmentioning
confidence: 99%
“…In the numerical optimization literature, null space algorithms for saddle point problems have been studied extensively, often called reduced Hessian methods; see the review paper (Benzi et al 2005) and the references therein. Null space algorithms, as opposed to the range space method of GGA (Todini and Pilati 1988), have also been applied for hydraulic analysis of water and gas pipe networks (Nielsen 1989;Rahal 1995;Elhay et al 2014;Todini and Rossman 2012). The three references (Nielsen 1989;Rahal 1995;Elhay et al 2014) differ in the way they generate the null space bases.…”
Section: Introductionmentioning
confidence: 99%
“…Null space algorithms, as opposed to the range space method of GGA (Todini and Pilati 1988), have also been applied for hydraulic analysis of water and gas pipe networks (Nielsen 1989;Rahal 1995;Elhay et al 2014;Todini and Rossman 2012). The three references (Nielsen 1989;Rahal 1995;Elhay et al 2014) differ in the way they generate the null space bases. Nielsen (1989) proposes the use of matrix row and column permutations to compute null space bases, whereas Rahal (1995) uses graph theoretic tools to solve what he called the co-tree formulation of the problem.…”
Section: Introductionmentioning
confidence: 99%